Hubungan perilaku Ibu dalam memanfaatkan pelayanan kesehatan selama kehamilan dengan kepatuhan ibu mengimunisasikan anaknya - Najma Sofia, Siswanto Agus Wilopo dan Djauhar Ismail (Berita Kedokteran Masyarakat (BKM), 2004)
Background: The report of SDK1 in the year of 2002-2003 stated that the complete immunization coverage in Indonesia was only 51 percent. Incomplete immunization status is one of the causal factors of low health status in children that finally will cause the high rate of morbidity and mortality. in the district of Belu, immunization coverage generally was still relatively low. That was 35,3 percent. The incomplete immunization status still occurred although the Department of Health and the Indonesian Pediatrics Association have arranged a schedule for children immunization considering certain time restrain. Various research showed that Mother's factor had a great influence in bringing the children for immunization. Objective: This research was aimed at finding out the relationship of mother's behavior in making use of modern health service during pregnancy especially antenatal care (ANC) with mother's compliance in bringing the children for immunization. Method: This research used a case control design. The sample was mothers who had children 12 to 59 months of age consisting of 114 samples as case and 114 samples as control. Chi-square test and logistic regression was performed to analyze quantitative data. This research was located in the district of Belu, Nusa Tenggara Timur. The location was selected based on data availability and the immunization coverage that was still relatively low. Result: The bivariable and multivariable analyses with 6 logistic regression models showed that the result was consistent; there was a significant relationship between behaviors of using health service during pregnancy with mother's compliance in bringing the children for immunization. Mother's education level and access to facility of health care also had significant relationship with mother's compliance in bringing her children for immunization. Conclusion: Three factor influenced the mother's compliance in bringing her children for immunization: mother's behavior in using health service during pregnancy, mother's education level, and access to facility of health care. Keywords: behavior, pregnancy, compliance, immunization